Experimental study on the hydrological performance of a permeable pavement. Issue 4 (21st April 2017) - Alsubih, Majed; Arthur, Scott; Wright, Grant; Allen, Deonie
Abstract: Permeable pavements play an essential role in urban drainage systems, making them the subject of great interest to both researchers and practitioners. However, previous studies have demonstrated a significant degree of uncertainty regarding both the hydrological performance and the maintenance requirements of this type of pavement. Within this context, the presented research involved the construction of a one metre square surface area of permeable pavement and a laboratory rainfall simulator to investigate the influence of rainfall intensity on the hydrologic response of permeable pavements. The design of the permeable pavement complied with the SuDS Manual guidance and British Standards ( BS 7533-13:2009 ). The laboratory test programme was designed to investigate the influence of rainfall intensity on the hydrologic response of permeable pavements. The results demonstrate that the hydrologic performance varied according to rainfall intensity. The total volume of discharge from the permeable pavement ranged between 8% to 60% of the inflow. More than 40% of the total rainfall from all rain events was temporarily detained within the structure. Permeable pavement design optimisation has therefore been tested in the study. The SuDS Manual guidance has been found to meet current optimisation requirements.